Β-Glucuronidase triggers extracellular MMAE release from an integrin-targeted conjugate. Issue 19 (25th April 2019) - López Rivas, Paula; Müller, Christoph; Breunig, Christian; Hechler, Torsten; Pahl, Andreas; Arosio, Daniela; Belvisi, Laura; Pignataro, Luca; Dal Corso, Alberto; Gennari, Cesare
Abstract : A non-internalizing conjugate targeting αv β3 integrin inhibits the proliferation of integrin-expressing cancer cells in the presence of β-glucuronidase. Abstract : A non-internalizing αv β3 integrin ligand was conjugated to the anticancer drug MMAE through a β-glucuronidase-responsive linker. In the presence of β-glucuronidase, only the conjugate bearing a PEG4 spacer inhibited the proliferation of integrin-expressing cancer cells at low nanomolar concentrations, indicating important structural requirements for the efficacy of these therapeutics.